1999
DOI: 10.1095/biolreprod61.3.629
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Pharmacological-Sensitivity Profile of Neoglycoprotein-Induced Acrosome Reaction in Mouse Spermatozoa1

Abstract: Mammalian spermatozoa undergo the acrosome reaction (AR) in response to the interaction of a carbohydrate-recognizing molecule(s) on the sperm plasma membrane (sperm surface receptor) and its complementary glycan (ligand) moiety(ies) on the zona pellucida (ZP). Previously, we demonstrated that a hexose (mannose) or two amino sugars (glucosaminyl or galactosaminyl residues) when covalently conjugated to a protein backbone (neoglycoproteins) mimicked the mouse ZP3 glycoprotein and induced the AR in capacitated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…the action of ZP3 glycoprotein and induce acrosome reaction in capacitated mouse [28,40] and human sperm [50]. The acrosome reaction-inducing ability of neoglycoprotein and the reduction of glycodelin binding after acrosome reaction requires the use of fixed, instead of live, sperm for characterization of the glycodelin-binding sites on sperm using neoglycoproteins; otherwise, equilibrium binding would have been impossible to achieve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the action of ZP3 glycoprotein and induce acrosome reaction in capacitated mouse [28,40] and human sperm [50]. The acrosome reaction-inducing ability of neoglycoprotein and the reduction of glycodelin binding after acrosome reaction requires the use of fixed, instead of live, sperm for characterization of the glycodelin-binding sites on sperm using neoglycoproteins; otherwise, equilibrium binding would have been impossible to achieve.…”
Section: Discussionmentioning
confidence: 99%
“…Neoglycoproteins are synthesized by linkage of specific carbohydrate residues to a protein backbone. They have been used to investigate the impact of a given carbohydrate moiety in cell-to-cell interactions [40,41]. The third objective of this study was to address the role of a single carbohydrate in neoglycoproteins and of selectins in the binding of glycodelin-A and -F to sperm.…”
Section: Introductionmentioning
confidence: 99%
“…NGPs, which have been proposed to act in a similar manner to human ZP, induce elevation of [Ca 2ϩ ] i and AR in human spermatozoa (37,43,44). NGP-induced AR is blocked by VOCC antagonists (44,45) and mibefradil, a semispecific blocker of T-type channels, blocks NGP-induced [Ca 2ϩ ] i signaling and AR with similar potency (37,46). Using molecular and immunohistochemical techniques, Benoff and colleagues (27) have provided evidence for the presence of a number of isoforms of the HVA ␣ 1C subunit in human testis and spermatozoa.…”
mentioning
confidence: 99%
“…In result, sperm -ZP binding was significantly decreased in the presence of BSA-Fuc (2.5-250 lg ml À1 ) or BSA-Gal (25-250 lg ml À1 ) (Fig. Although several kinds of monosugar linked to a BSA and or Lewis X -BSA mimicked ZP3 in mouse (Loeser et al, 1999;Hanna et al, 2004), we firstly reported that fucose-BSA can also inhibit sperm-ZP binding in mouse. Because the assay medium contained an excess amount of BSA, binding inhibition by these NGPs was not due to free BSA.…”
Section: Discussionmentioning
confidence: 90%
“…Glycans with a terminal Lewis X (Galb4[Fuca3]GlcNAc-R) or Lewis A (Galb3[Fuca4]GlcNAc) structure act as specific and potent inhibitors of a subset of sperm binding to ZP3 in mice (Johnston et al, 1998). Several studies have investigated whether neoglycoproteins (NGPs) synthesised by the linkage of specific carbohydrate residues to a protein backbone can mimic natural ZP glycoconjugates (Benoff et al, 1993(Benoff et al, , 1997Brandelli et al, 1995;Blackmore & Eisoldt, 1999;Loeser et al, 1999;Hanna et al, 2004;Rosano et al, 2007). Removal of the fucosyl residue from the Lewis X trisaccharide abolishes the glycan's ability to act as a competitive inhibitor of ZP3 binding.…”
Section: Introductionmentioning
confidence: 99%